2016
DOI: 10.1002/jcph.738
|View full text |Cite
|
Sign up to set email alerts
|

Compliance, Persistence, and Preferences Regarding Osteoporosis Treatment During Active Therapy or Drug Holiday

Abstract: Osteoporosis treatments reduce the risk of fractures by 30%-50%, but adherence after 1 year is only about 50%. Drug holiday, a period with no active treatment, is part of routine management. The objective of this study was to determine compliance and persistence with osteoporosis therapy among postmenopausal women and to assess attitudes regarding treatment resumption among patients on drug holiday. This was a prospective observational study of patients followed at a dedicated metabolic bone clinic September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Four of the studies did not report a direct association between patient preference and adherence to treatment, although this can likely be explained by factors related to the individual study. Considering the studies on osteoporosis, that by Eliasaf et al reported that their study included highly motivated patients, that compliance was higher than that previously reported in the literature, and that patients on drug holiday did not have a preference for medication (25). All these factors may have had a role in the lack of significant differences.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Four of the studies did not report a direct association between patient preference and adherence to treatment, although this can likely be explained by factors related to the individual study. Considering the studies on osteoporosis, that by Eliasaf et al reported that their study included highly motivated patients, that compliance was higher than that previously reported in the literature, and that patients on drug holiday did not have a preference for medication (25). All these factors may have had a role in the lack of significant differences.…”
Section: Discussionmentioning
confidence: 90%
“…In the study by Eliasaf et al, 80% of patients took their medication as directed (64% were on an oral medication, mostly bisphosphonates). However, in comparing treatments for osteoporosis, there was no preferred medication among patients on drug holiday (25). Freemantle carried out a 2-year randomized, crossover trial comparing subcutaneous denosumab every 6 months to oral alendronate once weekly, and reported that denosumab was associated with less nonadherence than alendronate in both years of the trial (first year, 11.9% vs. 23.4%; second year, 7.5% vs. 36.5%) (23).…”
Section: Resultsmentioning
confidence: 99%
“…Injectable medications including teriparatide, DEN, and ZOL had significantly higher persistence compared with oral medications such as raloxifene and oral bisphosphonates. 38 Injectable medications can overcome some of the disadvantages of oral medications such as cumbersome administration instructions and gastrointestinal side effects. 39 40 41 Tremblay et al’s population-based study reported persistence rates of DEN and ZOL were 63.3% and 74.8%, respectively, after two years.…”
Section: Discussionmentioning
confidence: 99%
“…Such a treatment gap with respect to recommended practice (14) has been observed in many other health systems. (15)(16)(17)(18)(19)(20) In France, densitometry has been fully reimbursed since 2006, is recommended in osteoporosis practice guidelines, and is widely available. In fact, France has the highest number of densitometry machines per head of population in Europe.…”
Section: Discussionmentioning
confidence: 99%